Socioeconomic impact of small-scale irrigation on household’s livelihood improvement in Bena-Tsemay district of South Omo zone, Southern Ethiopia - Asmera, A; Yidnekachew, A (International Journal of Agricultural Research, Innovation and Technology, 2022)
The study investigated the socioeconomic impacts of irrigated agriculture and factors affecting the decision of agro-pastoralists to participate in irrigation during 2017-2018. The result depends on cross-sectional data collected from a sample of 120 households of which 90 irrigation users and 30 non-users using a combination of purposive and random sampling. The data were analyzed using descriptive statistics and logistic regression to assess factors that affect participation in irrigation. The logistic regression model revealed that age, credit access, extension contact, distance to water, and labor force significantly affected the decision of given agro-pastoralists to participate in irrigation practices at less than 5% probability levels. This indicates that the explanatory variables included in the model influence the decision of agro-pastoralists to participate in irrigation practices. Therefore, the provision of credit service to allow rapid progress in introducing technologies like tractors for farming practices and frequent extension contact with irrigation users could enhance the productivity in the area. Int. J. Agril. Res. Innov. Tech. 11(2): 139-146, Dec 2021